TRANSFORMATION OF THE LANGUAGE COMMUNICATIVE FUNCTION IN THE PERIOD OF INFORMATIZATION - Дротянко, Л. Г. (Proceedings of the National Aviation University Series Philosophy Cultural, 2015)
The article deals with the analysis of the communication language dependence on culture and on the level of technical means of communication development, particularly on the use of informational-communicational technologies.